Variability in the Clock Face View Description of Femoral Tunnel Placement in ACL Reconstruction Using MRI-Based Bony Models - Kraeutler, Matthew J.; Patel, Kushal V.; Hosseini, Ali; Li, Guoan; Gill, Thomas J.; Bravman, Jonathan T. (The Journal of Knee Surgery, 2018)
Though controversial, the “clock face view” of the intercondylar notch remains a way some surgeons communicate regarding placement of the femoral tunnel in anterior cruciate ligament reconstruction. The purpose of this study was to quantify the differences in angle measurement between several previous descriptions of the clock face view by using a new reference standard. Three-Tesla magnetic resonance imaging (MRI) was used to scan 10 human knees to create three-dimensional MRI-based bony models which were used for measurements. A standardized clock face view was developed with the knee flexed to 90° using the junction of the cartilage and cortex of the medial and lateral surfaces of medial and lateral femoral condyles as the 3 o'clock and 9 o'clock, respectively, with the 12 o'clock established as the midpoint of the roof of the intercondylar notch. With the knee viewed at 90° of flexion, an “idealized” femoral tunnel position was plotted on the medial wall of the lateral femoral condyle at 30° (corresponding to the 10 o'clock or 2 o'clock position). The clock faces as described by Edwards et al, Heming et al, and Mochizuki et al were each then overlaid on this same model and the difference in measurement calculated. The average angles measured when the previously described clock faces were projected onto the idealized clock face view comparing a mark made at 30° were 47.7°, 7.2°, and 49.8° for the methods described by Edwards et al, Heming et al, and Mochizuki et al, respectively (all p < 0.001). Significant variation exists between angle measurements in simulated femoral tunnel placement based on the varying descriptions of the intercondylar clock face.
Keywords: anatomy; anterior cruciate ligament reconstruction; clock face view; magnetic resonance imaging